The chromatin-remodeling enzyme Smarca5 regulates erythrocyte aggregation via Keap1-Nrf2 signaling - Yanyan Ding (eLife Sciences Publications Ltd, 2021)
Although thrombosis has been extensively studied using various animal models, our understanding of the underlying mechanism remains elusive. Here, using zebrafish model, we demonstrated that smarca5-deficient red blood cells (RBCs) formed blood clots in the caudal vein plexus. We further used the anti-thrombosis drugs to treat smarca5zko1049a embryos and found that a thrombin inhibitor, argatroban, partially prevented blood clot formation in smarca5zko1049a. To explore the regulatory mechanism of smarca5 in RBC homeostasis, we profiled the chromatin accessibility landscape and transcriptome features in RBCs from smarca5zko1049a and their siblings and found that both the chromatin accessibility at the keap1a promoter and expression of keap1a were decreased. Keap1 is a suppressor protein of Nrf2, which is a major regulator of oxidative responses. We further identified that the expression of hmox1a, a downstream target of Keap1-Nrf2 signaling pathway, was markedly increased upon smarca5 deletion. Importantly, overexpression of keap1a or knockdown of hmox1a partially rescued the blood clot formation, suggesting that the disrupted Keap1-Nrf2 signaling is responsible for the RBC aggregation in smarca5 mutants. Together, our study using zebrafish smarca5 mutants characterizes a novel role for smarca5 in RBC aggregation, which may provide a new venous thrombosis animal model to support drug screening and pre-clinical therapeutic assessments to treat thrombosis.